The Effectiveness of R.A.F.T Strategy in Teaching Writing Narrative Text - Wahyuni, Sri; Verawaty, Nadya Resti (Proceeding International Conference on Education, 2024)
This study aims at investigating the effectiveness of R.A.F.T. strategy to teach writing narrative text. By employing quasi-experimental research design, the researchers administered R.A.F.T strategy for experimental class and the PLEASE strategy for control class to the tenth-grade students at a senior high school in Plemahan. The data are collected through writing tests. Due to the non-normal distribution of the data, the pre-test and post-test data were analyzed utilizing Mann-Whitney test with SPSS version 22. The result displayed that between experimental and control class has a difference. The mean score of the experimental group was 70.41 for pre-test and 86.00 for post-test, and the mean of the control group was 68.70 for pre-test and 82.12 for post-test. The computation outcome of mean value of experimental class students who are taught by R.A.F.T strategy attained higher scores than the scores of control class students who are taught by PLEASE strategy. The Mann-Whitney test output Z was at -2.804, and 0.005 for a significance value obtained. Determined by the decision-making criteria, the acceptance of Ha happened, and Ho was rejected, since 0.005 was below 0.05. It is summed up that utilizing R.A.F.T strategy for teaching narrative text writing to the tenth grade students of a senior high school in Plemahan is effective.